Ecoenzyme Is An Anti-Bacterial Material For Making Multi-Purpose Soap From Used Cooking Oil Case Study : Implementation Of The CSR Program PT Pertamina Patra Niaga Dppu Adi Sumarmo - RACHMADANI, Karin Alifia; SYAFIQ, Aji Nuafal; FATONAH, Siti; WIJAYANGGO, Anggit (PT Keberlanjutan Strategis Indonesia, 2023)
Used cooking oil comes from frying with the same cooking oil repeatedly. Using used cooking oil can pose a danger to the human body, and the continuous disposal of waste cooking oil is detrimental to the environment and human survival. Making soap in Ngudi Makmur Village, Ngemplak Sub-District, Boyololali Regency with the addition of Eco Enzyme as an anti-bacterial additive, where eco enzyme itself has chemical properties that can be used as multipurpose soap. Used cooking oil obtained from Ngudi Makmur Village, Ngemplak District, Boyolali Regency produces 50 kg. The multipurpose soap made by the women of Ngudi Makmur Village had 210 bottles. Packaging per bottle of 330 ml – period December 2022-March 2023..